The pH of the main Brazilian commercial moisturizers and liquid soaps: Considerations on the repair of the skin barrier - Gonçalves, Giovana M. [UNESP]; Miot, Hélio Amante [UNESP]; Brianezi, Gabrielli [UNESP] (FapUNIFESP (SciELO), 2017)
The pH of the skin is slightly acidic (4.6 to 5.8) which is important for appropriate antibacterial, antifungal, constitution of barrier function, as well as structuring and maturation of the stratum corneum. This study aimed to evaluate the pH of the main commercial moisturizers and liquid soaps in Brazil. Thus, pH of the products was quantified by pH meter in three measurements. A total of 38 moisturizers and six commercial liquid soaps were evaluated. Mean pH of 63% and 50% of the moisturizing and liquid soaps presented results above 5.5, disfavoring repair, function, and synthesis of dermal barrier.
Keywords: Atopic; Dermatitis; Hydrogen-Ion concentration; Soaps; Wetting agents